Homecoming (Hekima Review, 2010)
The dogs and cats sit around the fireplaceLight pierce the dark nightDrums sing the old songs,Muffled, the song drown in darknessRed eyes tears from the smoke drops.Words roll from the silenced drums.Words, words, words, a muffled nipple.